2012
DOI: 10.4278/ajhp.110107-arb-8
|View full text |Cite
|
Sign up to set email alerts
|

Medics as a Channel for Worksite Health Promotion in Remote Global Locations

Abstract: When provided with appropriate tools, medics may be an ideal channel for health promotion in remote worksites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Fourteen relevant articles met the inclusion criteria for synthesis. Studies were predominantly observational, including four descriptive studies, 2,5,21,22 two comparative case studies, 23,24 one conceptual study, 25 one Quasi-experimental post-test-only design, 26 five literature reviews 3,[27][28][29][30] and an open-ended survey instrument. 31 Key themes arising in the literature included the geographically dependent nature of the needs of rural and remote communities, particularly those related to health workforce sustainability problems, specific community needs, a multidisciplinary response to emergency care and the paramedic scope of practice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen relevant articles met the inclusion criteria for synthesis. Studies were predominantly observational, including four descriptive studies, 2,5,21,22 two comparative case studies, 23,24 one conceptual study, 25 one Quasi-experimental post-test-only design, 26 five literature reviews 3,[27][28][29][30] and an open-ended survey instrument. 31 Key themes arising in the literature included the geographically dependent nature of the needs of rural and remote communities, particularly those related to health workforce sustainability problems, specific community needs, a multidisciplinary response to emergency care and the paramedic scope of practice.…”
Section: Resultsmentioning
confidence: 99%
“…Paramedics were found to have the time and motivation required to deliver health promotion activities, but were underequipped with skills and materials. 26 That study found that medics in remote worksites may be well served to conduct health promotion when provided with appropriate tools.…”
Section: Health Promotionmentioning
confidence: 97%
See 3 more Smart Citations